Some issues in understanding spirituality as relational - Venkataraman, Prabhu; Konwar, Bharat (2019)
In the present literature, understanding and interpretation of spirituality has moved from the transcendent to the relational aspect of the human being. This movement has been necessitated by shortcomings in understanding spirituality as transcendent. The idea of transcendent is unverifiable and subjective. Moreover, it is possible in the context of specific cultural and religious traditions, but not in a multicultural context. Spirituality in its relational sense is interpreted as a process of developing an intrinsic human capacity that motivates people to search for meaning, purpose, and contribution to life in a social context. The relational aspect of spirituality can be understood as 'thoughtful love of life' leading to what may be termed 'naturalized spirituality'. However, understanding the relational aspect of spirituality has its own problems. This paper indicates some limitations to understanding spirituality as relational and argues that, rather than aiding an understanding of the concept, it creates more confusion. This is because the notion of 'relational' (i) does not exclude the transcendent, and (ii) does not distinguish between what is spiritual and what is not.
Keywords: Spirituality; Conceptualization; Relational; Transcendent